(untitled)
The recent global fits of neutrino oscillation data is pointing towards non-maximal value of atmospheric neutrino mixing angle (θ_23) and normal hierarchical neutrino masses at about 1.6σ and 2.5σ confidence level, respectively. The neutrino mixing matrix with cobimaximal (CBM) pattern is known to predict maximal value of θ_23 (=45^o) and Dirac CP phase δ_CP =± π/2 while the solar (θ_12) and reactor (θ_13) mixing angles are arbitrary. In this work, we study a simple deviation from this mixing pattern in order to accommodate non-maximal values of θ_23. Also, we have calculated the prediction for Jarlskog CP rephasing invariant J_CP , sensitive to CP violation measured in the neutrino oscillation experiments., number=6, journal=Письма в ЭЧАЯ, year=2024, month=May